In vitro activity of mecillinam, temocillin and nitroxoline against MDR Enterobacterales. Issue 3 (16th June 2022) - Plambeck, Lars; Fuchs, Frieder; Sattler, Janko; Hamprecht, Axel
Abstract: Background: With increasing resistance to common antibiotics the treatment of urinary tract infections has become challenging and alternative therapeutic options are needed. In the present study, we evaluate the activity of three older and less frequently used antibiotics against MDR Enterobacterales. Methods: Susceptibility of mecillinam, temocillin and nitroxoline was assessed in Enterobacterales isolated from urinary specimens with elevated MICs of third-generation cephalosporins. Susceptibility was determined by the recommended reference MIC methods and additionally by disc diffusion. All isolates were characterized for common β-lactamases by phenotypic and molecular assays. Results: In total 394 Enterobacterales were included. The most common resistance mechanisms were ESBLs ( n  = 273), AmpC ( n  = 132), carbapenemases [ n  = 12, including OXA-48-like ( n  = 8), VIM ( n  = 2), KPC ( n  = 1) and NDM ( n  = 1)] or others ( n  = 2). Resistance was observed in 59% of isolates to ceftazidime, in 41% to piperacillin/tazobactam and in 54% to ciprofloxacin. In comparison, resistance was less frequent against mecillinam (15%), temocillin (13%) or nitroxoline (2%). Mecillinam showed higher activity in Enterobacter spp., Escherichia coli and in OXA-48-like-producing isolates compared with temocillin, which was more active in Proteus mirabilis and in ESBL-producing isolates. Activity of nitroxoline was high against all isolates, including carbapenemase-producing isolates. Correlation between disc diffusion and MIC methods was good for mecillinam and moderate for temocillin and nitroxoline. Conclusions: Mecillinam, temocillin and nitroxoline show good to excellent in vitro activity in MDR Enterobacterales. The activity of mecillinam and temocillin was higher in certain species and restricted depending on β-lactamase production while nitroxoline showed universally high activity irrespective of species or β-lactamase present.